Health and family life education: Empowering young people with skills for healthy living - UNICEF Caribbean Area Office (UNICEF Caribbean Area Office, 1998)
This document provides information on major problems and issues facing children and young people in the Caribbean, and explores how health and family life education (HFLE) could help in better equipping young people to cope more effectively with the challenges they face. It also gives an overview of the CARICOM Multi-Agency Health and Family Life Education Project. In addition, it describes the scope and content of a lifeskills-based HFLE curriculum, presents a rationale for strengthening HFLE in schools, explores the importance of the roles of the school supervisors and principals in the teaching of HFLE in school, and explores the development of new partnerships.
Keywords: health and family life education; HFLE; youth empowerment